Preliminary results of the agroecological performance assessment of milk-producing farms in the Bobo-Dioulasso production basin using the HOLPA tool - Orounladji, Boko Michel; Kouakou, Patrice; Ouedraogo, Adama; Sanogo, Souleymane; Sib, Ollo; Vall, Eric (2024)
This report summarizes all the activities carried out in 2023 to assess the performance of agroecological farming systems based on evidence gathered in the Bobo-Dioulasso dairy basin.